Vasopressor Therapy in the Intensive Care Unit - Russell, James A.; Gordon, Anthony C.; Williams, Mark D.; Boyd, John H.; Walley, Keith R.; Kissoon, Niranjan (Seminars in Respiratory and Critical Care Medicine, 2020)
After fluid administration for vasodilatory shock, vasopressors are commonly infused. Causes of vasodilatory shock include septic shock, post-cardiovascular surgery, post-acute myocardial infarction, postsurgery, other causes of an intense systemic inflammatory response, and drug -associated anaphylaxis. Therapeutic vasopressors are hormones that activate receptors—adrenergic: α1, α2, β1, β2; angiotensin II: AG1, AG2; vasopressin: AVPR1a, AVPR1B, AVPR2; dopamine: DA1, DA2. Vasopressor choice and dose vary widely because of patient and physician practice heterogeneity. Vasopressor adverse effects are excessive vasoconstriction causing organ ischemia/infarction, hyperglycemia, hyperlactatemia, tachycardia, and tachyarrhythmias. To date, no randomized controlled trial (RCT) of vasopressors has shown a decreased 28-day mortality rate. There is a need for evidence regarding alternative vasopressors as first-line vasopressors. We emphasize that vasopressors should be administered simultaneously with fluid replacement to prevent and decrease duration of hypotension in shock with vasodilation. Norepinephrine is the first-choice vasopressor in septic and vasodilatory shock. Interventions that decrease norepinephrine dose (vasopressin, angiotensin II) have not decreased 28-day mortality significantly. In patients not responsive to norepinephrine, vasopressin or epinephrine may be added. Angiotensin II may be useful for rapid resuscitation of profoundly hypotensive patients. Inotropic agent(s) (e.g., dobutamine) may be needed if vasopressors decrease ventricular contractility. Dopamine has fallen to almost no-use recommendation because of adverse effects; angiotensin II is available clinically; there are potent vasopressors with scant literature (e.g., methylene blue); and the novel V1a agonist selepressin missed on its pivotal RCT primary outcome. In pediatric septic shock, vasopressors, epinephrine, and norepinephrine are recommended equally because there is no clear evidence that supports the use of one vasoactive agent. Dopamine is recommended when epinephrine or norepinephrine is not available. New strategies include perhaps patients will be started on several vasopressors with complementary mechanisms of action, patients may be selected for particular vasopressors according to predictive biomarkers, and novel vasopressors may emerge with fewer adverse effects.
Keywords: septic shock; norepinephrine; epinephrine; phenylephrine; dopamine; angiotensin II; vasopressin; terlipressin; selepressin